2021
DOI: 10.3389/fnut.2021.730037
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal High-Fat Diet on Bone Microarchitecture in Offspring

Abstract: The incidence of obesity in women of reproductive age has significantly increased over the past 100 years. There is a well-established connection between maternal obesity during pregnancy and an increased risk of developing non-communicable cardiometabolic diseases in her offspring. This mini-review focuses on evidence examining the effect of maternal high-fat diet (HFD) on skeletal development and bone health in later life in offspring. The majority of rodent studies indicate that maternal HFD generally negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…They found an association of high maternal TC at mid-pregnancy with altered development in these infants. These results are in agreement with pre-clinical findings and suggest that a high-fat diet during pregnancy can disturb the growth and development of the offspring (13).…”
supporting
confidence: 91%
“…They found an association of high maternal TC at mid-pregnancy with altered development in these infants. These results are in agreement with pre-clinical findings and suggest that a high-fat diet during pregnancy can disturb the growth and development of the offspring (13).…”
supporting
confidence: 91%
“…Since the maternal supply of cholesterol to the fetus plays an important role in the development of the fetal nervous and vascular system ( 21 23 ), the maternal blood level of total cholesterol (TC) is linearly associated with the infant’s birth size ( 24 27 ). In contrast, findings from recent animal experimental studies indicated that maternal high-fat diet induces impairment of lung development and function ( 28 , 29 ), skeletal muscle ( 30 ), and/or bone mass development ( 31 33 ) and growth pattern ( 34 ) in the offspring. Although maternal lipids in the critical fetal period can influence infant growth, no study has investigated whether the maternal lipid blood level is associated with No-CU among SGA infants.…”
Section: Introductionmentioning
confidence: 84%
“…This is the first human study to report results that are consistent with those of previous animal experimental studies. A mini-review ( 31 ) reported that majority of rodent studies indicate that maternal high-fat diet adversely affects both embryonic bone development and bone volume in adult animals ( 30 , 32 , 33 ). In addition, Mikovic et al.…”
Section: Discussionmentioning
confidence: 99%
“…We found that mice fed a HFD had decreased trabecular bone and cortical thickness compared to mice fed a LFD. While we did not further explore the cellular mechanisms underlying the bone loss in the current study, this occurrence has been well documented in both female and male rodents ( 49–53 ) and occurs via increased bone resorption ( 54 ) and decreased bone formation. ( 55 ) The HFD in our study consisted of 46% calories from fat, which is lower than the 60% fat diets used in many studies.…”
Section: Discussionmentioning
confidence: 99%